O debate político sobre a legalização do aborto no Brasil (1980-2020) : neoconservadorismo e políticas antigênero na América Latina - Maria Clara de Mendonça Maia (2022)
This dissertation discusses the general theme of neoconservatism and anti-gender policies in Brazil, with a focus on the issue of abortion. The general objective is to identify if and how the current movement of neoconservatism has interfered in the agenda on the legalization of abortion in Brazil. This work builds a multicentered narrative for the posed question, mobilizing the critical discursive fields of Feminist Political Theory and other critical approaches, in the period started in the 1980s, with the end of the military regimes and the beginning of the redemocratization processes, until 2020. Considering the abortion debate, the specific objectives are: to analyze the relationships between the dynamics of neoconservatism and the movements anti-gender in Latin America, through the specificities of the Brazilian case; explain the role of feminist and anti-gender movements in relation to the theme between 1980 and 2020; understand how the articulation of the anti-gender agenda took place, specifically in relation to the criminalization of abortion in the Legislative scope for the established period. Thus, the hypotheses of this Dissertation are presented as followed: (1) with the expansion of neoconservative movements in Latin America, a new framework of increasing conservatism on the subject is established in the public debate regarding the legalization of abortion in Brazil; (2) facing a context of political, moral and social transformations, the political agenda on the legalization of abortion recedes in the country. This is an exploratory and qualitative research, with a single case study approach, in which the phenomenon of neoconservatism and anti-gender policies, as well as the performance of feminist and anti-gender movements, will be studied considering the abortion agenda in the Brazilian legislative system.